Adaptation and validation of the Chinese version of the lung cancer screening health belief scales - Yu-an Lin; Lisa Carter-Harris; Jia-ni Yang; Xiu jing Lin; Fei fei Huang (BMC, 2022)
Abstract Background Health belief is an important factor affecting lung cancer screening in high-risk population, but the research based on Chinese cultural background is still insufficient. Therefore, we adapted the English version of the Lung Cancer Screening Health Belief Scales (LCSHB) into the Chinese version (LCSHB-C) and examined its psychometric characteristics. Methods After obtaining authorization from the original author, the LCSHB-C was adapted based upon Brislin's translation model. Using a variety of community-based recruitment methods, a total of 353 participants were recruited in Fuzhou, Fujian province, China to complete the questionnaires. We combined the classical test theory and item response theory to examine the psychometric properties of the LCSHB-C. Results The Cronbach's alpha for the four subscales ranged from 0.83 ~ 0.93. The content validity index for the four subscales was ranged from 0.87 ~ 1.0. Confirmatory factor analysis supported each subscale structure model fit well. Rasch analysis results further validated the reliability and validity of the four subscales. The person reliability and separation index of each subscale ranged from 0.77 to 0.87 and 1.83 to 2.63, respectively. Conclusions The LCSHB-C is a reliable and valid instrument used to measure health beliefs related to lung cancer screening among those high-risk for lung cancer in China, which facilitates the development of lung cancer screening programs and promotes the "three early prevention strategies" of lung cancer (i.e.,early detection, early diagnosis and early treatment).